Labour Economics with a Comprehensive Analysis of Wage Determination Mechanisms and Income Inequality in Developing Countries - Priya Darshan Waila; Puran Singh (Journal of Advanced Research in Economics and Business Management, 2026)
The increased wage and income inequality has become a major issue in developing economies, even though there have been financial booms and globalisation. This paper gives an in-depth study of the wage determination procedures and their consequences for income inequality by combining the market-driven labour economics theories with the institutional and structural approach. It analyses the interplay between labour supply-demand relationships with marginal productivity and the accumulation of human capital with wage-setting institutions like minimum wage, collective bargaining and labour regulations. Special focus is made on the role of informality and labour market segmentation, which undermine the relationship between productivity and wages and put persistent wage punishment on substantial groups of the labour force. The paper also presents the effects of global economic integration by involving global value chains, outsourcing, migration, and the proliferation of digital labour platforms. Although these processes have generated job vacancies, they have increased competitive wages and wage insecurity, particularly for the low- and medium-skilled workers. Based on the case studies in the developing economies, such as India, Brazil, and South Africa, the analysis demonstrates that wage inequality can be decreased through minimum wage reforms and institutional interventions when properly implemented, but their effectiveness is limited in highly informal labour markets. These findings collectively point out that the increasing inequality is not an unavoidable factor of globalisation or technological transformation, but rather it is heavily influenced by local institutions and policy options. To get more inclusive labour market results, it is necessary to strengthen wage-setting mechanisms, increase the level of formal employment, and make skill development and productive job creation more aligned.